Reproductive performance of dairy cows with delayed uterine involution under hormonal therapy with estradiol cypionate and estradiol benzoate - Ruiz García, Luis Felipe (2017)
The aim of this study was to evaluate the reproductive performance of dairy cows with delayed uterine involution under hormonal treatment with estradiol cypionate (CE2) and estradiol benzoate (BE2) between 36 and 49 days after parturition and a group of dairy cows with normal uterine involution. A total of 349 dairy cows with delayed uterine involution and 127 dairy cows without delayed uterine involution from a commercial farm in Lima, Peru were used. The BE2 treatment consisted of the i.m. application of 3 doses of 5 mg at 2-day interval and the CE2 treatment consisted of the i.m. application of 2 doses of 4 mg at 4-day interval. The parameters evaluated were calving-to-conception interval (IPC), services per conception (NSC), conception rate at first service (P1S) and the pregnancy rate at 200 days (P200D). In addition, the likelihood of get pregnant according to the days in lactation using Cox proportional hazards model. Both the IPC and the NSC were lower in cows treated with CE2 (122.1 days and 1.3 respectively) that in cows treated with BE2 (138.4 days and 1.5, respectively (p<0.05). The P1S and P200D were similar in cows with CE2 (49.3 and 47.7% respectively) and in cows treated with BE2 (36.7 and 50.2% respectively). In addition, cows treated with CE2 were 1.6 times more likely to conceive sooner than cows treated with BE2 (p<0.01). The application of estradiol cypionate in relation to oestradiol benzoate is recommended to improve the reproductive performance in dairy cows with delayed uterine involution.